2015
DOI: 10.1097/aog.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Emergency Department Visits and Complications After Abortion

Abstract: OBJECTIVE: To conduct a retrospective observational cohort study to estimate the abortion complication rate, including those diagnosed or treated at emergency departments (EDs). METHODS:Using 2009-2010 abortion data among women covered by the fee-for-service California Medicaid program and all subsequent health care for 6 weeks after having an abortion, we analyzed reasons for ED visits and estimated the abortion-related complication rate and the adjusted relative risk. Complications were defined as receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
97
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 221 publications
(122 citation statements)
references
References 18 publications
17
97
1
1
Order By: Relevance
“…Collectively more women in the dilators-alone arm had uterine reaspiration, a cervical laceration requiring sutures, or hemorrhage requiring intervention beyond uterotonics than women in the misoprostol or mifepristone arms; although warranting further investigation, these differences were not statistically significant. Although the complication rate of 10% in the dilators-alone arm appears higher than rates reported in large retrospective studies of secondtrimester abortion, 3 it is comparable to rates reported in other prospective trials of cervical preparation before dilation and evacuation at 20-23 6/7 weeks of gestation. 13 We anticipated a priori that we would have inadequate power to measure complications as our primary outcome, which is why we chose the primary outcome of operative time.…”
Section: Discussionsupporting
confidence: 75%
“…Collectively more women in the dilators-alone arm had uterine reaspiration, a cervical laceration requiring sutures, or hemorrhage requiring intervention beyond uterotonics than women in the misoprostol or mifepristone arms; although warranting further investigation, these differences were not statistically significant. Although the complication rate of 10% in the dilators-alone arm appears higher than rates reported in large retrospective studies of secondtrimester abortion, 3 it is comparable to rates reported in other prospective trials of cervical preparation before dilation and evacuation at 20-23 6/7 weeks of gestation. 13 We anticipated a priori that we would have inadequate power to measure complications as our primary outcome, which is why we chose the primary outcome of operative time.…”
Section: Discussionsupporting
confidence: 75%
“…Of the 12 ASC and hospital-based studies that reported on this intervention, only two reported transfusion was necessary, and each study cited only one case out of 6,093 total abortions [45,56]. A transfusion was necessary in <0.1% of US office-and hospital-based abortions in the third phase of the US-based Joint Program for the Study of Abortion (JPSA-III), [71] and Upadhyay et al's [73] study using Medi-Cal claims, which included a total of 88,755 first-trimester procedures.…”
Section: Minor Interventions and Transfusion For Hemorrhage Or Excessmentioning
confidence: 92%
“…Niinimäki et al [74] combined ICD-10 codes for surgical interventions with those for cervical lacerations and any uterine perforation in Finnish registry data. The 0.6% of abortions requiring abdominal procedures in that study is likely an overestimate, since another claims-based study reported <0.1% of first-trimester aspiration abortions had a CPT code for an abdominal surgical procedure [73].…”
Section: Abdominal Surgerymentioning
confidence: 97%
“…Overall, abortion is very safe; a first-trimester abortion is one of the safest medical procedures and carries minimal risk-less than 0.05%-of major complications that might need hospital care [53][54][55]. Mortality is extremely rare when abortion is performed by qualified, competent licensed healthcare providers and occurs early in pregnancy [56].…”
Section: Are Abortions Safe?mentioning
confidence: 99%